The Shift of Indonesian Political Culture from Moral Legitimacy to Capital Legitimacy - Musa, Ali Masykur (International Journal of Criminology and Sociology, 2022)
This research is the result of a study of the shift in culture and political practices in Indonesia from moral legitimacy to capital legitimacy. This research is based on the concept of political culture, political theory, the practice of political meaning, and the views of several political observers. The results of research on the changes and political culture in Indonesia. The embodiment of political practice is related to political actors who practice what is called homo homini lupus which is justified. The shift from moral legitimacy to behavioral capital legitimacy is only measured in material terms and this is not in line with the Pancasila Democratic Ethics, which in principle argues that all political processes must be based on the value of struggle for the Indonesian State and Nation. Political pragmatism as it is today will be linked to political capitalization and liberalization, all of which are based on 2 (two) determinants, namely, money and power. Money and power are everything that must be obtained to maintain power itself, regardless of whether the process is against ethics and hurts the conscience of the sovereign people.